Where they found her - McCreight, Kimberly (New York, NY : HarperLuxe, 2015)
At the end of a long winter in well-to-do Ridgedale, New Jersey, the body of an infant is discovered in the woods near the town's prestigious university campus. When freelance journalist, and recent Ridgedale transplant, Molly Sanderson is unexpectedly called upon to cover the story for the Ridgedale Reader, it's a risk, given the severe depression that followed the loss of her own baby. But the bigger threat comes when Molly unearths some of Ridgedale's darkest secrets, including a string of unreported sexual assaults going back twenty years.
Keywords: Murder -- Investigation -- Fiction; Large type books; Women journalists -- Fiction; Infanticide -- Fiction; Suspense fiction; New Jersey -- Fiction; Detective and mystery fiction; Suspense fiction